(untitled) (International Congress on Economics, Management and Business Studies, 2026)
One of the main features of modern society is the need for enterprising, competitive, competent specialists in various spheres of social life, in production activities, including in the field of informatics. To become a sought-after specialist, one must have sufficient education. The higher the level of education, the higher the professional and social mobility. In the complex conditions of modern life, one must be able to make independent decisions and quickly respond to changes. Therefore, the ability to think independently, analyze, make plans and create projects is becoming increasingly important today.